1994
DOI: 10.1007/bf02245453
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotics, clozapine and sulpiride do not antagonise amphetamine-induced stereotyped locomotion

Abstract: An automated tracking system which converted an animal's path between quadrants of a circular open field into a series of trips was used to analyse stereotyped locomotion in amphetamine treated rats. Amphetamine (3.5 mg/kg) increased the horizontal distance moved and the number and proportion of thigmotaxic trips around the perimeter of the apparatus (length 4 trips). To investigate the hypothesis that classic antipsychotics, but not atypical antipsychotics, would antagonise the repetitive boundary patrolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The behavioral studies using rats, antagonism of dopamine agonist-induced hyperlocomotion (Janssen et al, 1965;Ogren et al, 1984;Gustafsson and Christensson, 1990;Moore and Kenyon, 1994) and conditioned avoidance response (CAR) paradigm (Cook et al, 1955;Davidson and Weidley, 1976;Arnt, 1982; for review, see Wadenberg et al, 1999) have traditionally been used to predict the antipsychotic efficacy of novel agent. In the present study, YKP1447 dose-dependently inhibited d-amphetamine-induced hyperlocomotion activity in rats, indicating the antipsychotic action of YKP1447.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral studies using rats, antagonism of dopamine agonist-induced hyperlocomotion (Janssen et al, 1965;Ogren et al, 1984;Gustafsson and Christensson, 1990;Moore and Kenyon, 1994) and conditioned avoidance response (CAR) paradigm (Cook et al, 1955;Davidson and Weidley, 1976;Arnt, 1982; for review, see Wadenberg et al, 1999) have traditionally been used to predict the antipsychotic efficacy of novel agent. In the present study, YKP1447 dose-dependently inhibited d-amphetamine-induced hyperlocomotion activity in rats, indicating the antipsychotic action of YKP1447.…”
Section: Discussionmentioning
confidence: 99%
“…When administered to animals, these drugs elicit a pattern of repetitive behavior (stereotypy), which requires an intact dopaminergic projection to the striatum and other forebrain sites (Dunnett and Robbins, 1992;Rebec and Bashore, 1984). In fact, amphetamine not only releases striatal dopamine (Butcher et al, 1988;Kuczenski and Segal, 1989;Zetterstr6m et al, 1983), but the behavioral effects of this drug are blocked either by neuroleptics (e.g., Megens et al, 1992;Moore and Kenyon, 1994;Ridley et al, 1979;Rollema et al, 1976;Tschanz and Rebec, 1988), which block dopamine receptors (Ellenbroek, 1993;Reynolds, 1994;Seeman, 1980), or by destruction of dopaminergic terminals in the striatum (Creese and Iversen, 1975;Fibiger et al, 1973;Fink and Smith, 1980;Kelly et al, 1975). Thus, stria.tal dopamine has been linked not only to the behavioral effects of amphetamine but also to idiopathic schizophrenia (Carlsson, 1978;Laduron, 1989;Seeman and Van Tol, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…The locomotor stereotypy produced by methylphenidate and amfonelic acid is blocked by haloperidol, but not by CLOZ (Mueller, 1993). However, CLOZ has been reported to block selective components of amphetamine-induced stereotypy (Tschanz and Rebec, 1989), but does not antagonize amphetamine-induced stereotyped locomotion (Moore and Kenyon, 1994). It has been suggested that CLOZ produces catalepsy, although this effect is not dose-dependent and is not very marked or intense (Costall and Naylor, 1975).…”
Section: Studies Addressing Cloz's Selectivity For the Mesolimbic Sysmentioning
confidence: 96%